Avaliação do crescimento tumoral e do comportamento animal com o uso de propranolol em um modelo de melanoma murino - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Through the tyrosinase pathway, melanin and catecholamines originate, both in melanoma disorder. Catecholamines, which act on the sympathetic nervous system, function naturally as neurotransmitters or hormones and have been linked to tumor progression and psychological and behavioral changes. In this sense, the purpose of this work was to evaluate the use of the β-blocker propranolol in tumor progression and in behavioral changes such as anxiety and depression in murine melanoma. The in vitro MTT cell viability assay (3- (4,5-dimethylthiazol-2-yl) -2,5 diphenyltetrazolium bromide) was performed with propranolol in concentrations 0.01, 0.1, 0.3, 1.0, 3.0, 10 mM and evaluated after 24, 48 and 72 hours using B16F10 cells. For the in vivo test, C57BL6/J mice were used, submitted to the implantation of tumor cells and subsequently treated and evaluated for 20 days for tumor growth with volume determination. The groups were composed of healthy control mice and treated with oral solution of propranolol at doses of 10 and 40 mg/kg/day and mice with control melanoma and treated with oral solution of propranolol at doses of 10 and 40 mg/kg/day. During the treatment period, behavioral tests of open field, forced swimming, elevated plus maze and test of hiding spheres in initial tumor and in consolidated tumor were performed. As a result of the MTT viability test, propranolol decreased cell viability at concentrations of 0.3, 1.0, 3.0, 10 mM in 24, 48 and 72 hours. In the in vivo experimentation, treatment with propranolol decreased tumor growth at a dose of 40 mg/kg/day in 15 days of treatment. The open field test showed no difference in time 1 and there was a reduction in locomotion in time 2 in the propranolol groups treated with 10 and 40 mg and in the group with melanoma 40 mg, when compared to the healthy control. The elevated plus-maze tests and the marble-burying test showed no statistical difference in any of the evaluated times. The forced swim test showed a statistical difference in the swimming time of the groups with melanoma 40 mg and healthy groups treated with propranolol 10 mg and 40 mg and in immobility behavior all groups remained immobile longer than the healthy control in time 1. It was concluded that propranolol may have an important role in tumor progression due to in vitro cytotoxicity and inhibitory to tumor growth measured in vivo and in behavioral tests propranolol provided a depressive effect on the swim, not being effective as an anxiolytic or antidepressant and altered accordingly discrete form motility in tests over time 2 making it difficult to differentiate an effect on locomotion.
Keywords: melanoma; propranolol; comportamento; melanoma; propranolol; behavior; CNPQ::CIENCIAS DA SAUDE::FARMACIA